2001
DOI: 10.1136/bjo.85.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Antegrade balloon dilatation of nasolacrimal duct obstruction in adults

Abstract: Aims-To determine the eYcacy of antegrade balloon dilatation of postsaccal lacrimal stenosis in adults. Methods-Balloon dilatation was performed in a series of 30 patients with complete nasolacrimal duct obstructions and epiphora. Obstruction was diagnosed by canalicular irrigation and transcanalicular endoscopic examination of the lacrimal pathway. Except for four cases in which general anaesthesia was applied, the procedure was performed under local anaesthesia. The Lacricath balloon catheter set was used. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
4
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
0
22
4
3
Order By: Relevance
“…Die Dacryozystorhinostomie (DCR) wird trotz bestehender moderner Verfahren der endokanalikulären, mikroendoskopischen Tränenwegschirurgie als am längsten bewährte, unverzichtbare Methode zur operativen Behandlung bei Tränenwegsobstruktio-nen eingesetzt. Das Operationsverfahren bei einer Dacryozystorhinostomie kann extern durch einen Hautschnitt über der Crista lacrimalis erfolgen oder intern, transnasal durch mikroskopische, rein endoskopische oder endoskopisch lasergestützte Verfahren [1][2][3][4]. Die externe Dacryozystorhinostomie wurde erstmals 1904 vom italienischen Rhinologen Addeo Toti beschrieben [5].…”
unclassified
“…Die Dacryozystorhinostomie (DCR) wird trotz bestehender moderner Verfahren der endokanalikulären, mikroendoskopischen Tränenwegschirurgie als am längsten bewährte, unverzichtbare Methode zur operativen Behandlung bei Tränenwegsobstruktio-nen eingesetzt. Das Operationsverfahren bei einer Dacryozystorhinostomie kann extern durch einen Hautschnitt über der Crista lacrimalis erfolgen oder intern, transnasal durch mikroskopische, rein endoskopische oder endoskopisch lasergestützte Verfahren [1][2][3][4]. Die externe Dacryozystorhinostomie wurde erstmals 1904 vom italienischen Rhinologen Addeo Toti beschrieben [5].…”
unclassified
“…6 -9 The reported munk at follow-up success of dacryocystoplasty alone ranges widely, from 25% to 50% 6,8 to 90%. 9,11 When (antegrade) dacryocystoplasty was combined with silicone intubation, two studies showed a six-month success rate of 56% to 60% in patients with incomplete NLD obstruction. 2,15 Kashkouli and associates recently compared endoscopically assisted balloon dacryocystoplasty and silicone intubation with silicone intubation alone in adults in a retrospective nonrandomized case series.…”
Section: Discussionmentioning
confidence: 99%
“…The catheter was withdrawn only after the balloon was deflated completely. 11 Next, bicanalicular silicone intubation was performed, using the Ritleng system (P. Ritleng, Issy-lesMoulineux, France). The two silicone tubes were tied together with a polypropylene 6-0 suture and was fixated to the lateral wall of the nose.…”
Section: Between April 1 2000 and December 31 2005 We Includedmentioning
confidence: 99%
“…In a similar study, Kuchar and Steinkogler found that at one year the success rate was 73%. 49 Several studies have reviewed the short-and long-term outcomes of retrograde dacryocystoplasty in adults. [50][51][52] Fenton et al reported an overall re-obstruction rate of 29% at one year, but 69% of those with initially complete obstruction failed by one year.…”
Section: Balloon Dacryocystoplastymentioning
confidence: 99%